2021
DOI: 10.1007/s10096-021-04213-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rapid multiplex PCR on management of antibiotic therapy in COVID-19-positive patients hospitalized in intensive care unit

Abstract: Because the diagnosis of co/superinfection in COVID-19 patients is challenging, empirical antibiotic therapy is frequently initiated until microbiological analysis results. We evaluated the performance and the impact of the BioFire® FilmArray® Pneumonia plus Panel on 112 respiratory samples from 67 COVID-19 ICU patients suspected of co/superinfections. Globally, the sensitivity and specificity of the test were 89.3% and 99.1%, respectively. Positive tests led to antibiotic initiation or adaptation in 15% of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 21 publications
3
52
0
2
Order By: Relevance
“…Excluded studies were comprised of 12 duplicates studies, 96 non-PN/PN plus Panel studies, 18 review articles or position statements, 17 non-clinical or non-human studies, two commentaries, three non-SARS-CoV-2 study, and one study due to insufficient data for evaluating incidence of co-detections related to PN Panel [Khurana et al, 2021] . After removing duplicate and non-applicable studies, seven studies with 558 patients were included for the systematic review and meta-analyses ( Table 1 , Supplementary Table 2) [ Camelena et al, 2021 , Kolenda et al, 2020 , Verroken et al, 2020 , Kreitmann et al, 2020 , Contou et al, 2020 , Foschi et al, 2021 , Maataoui et al, 2021 ]. Studies included a study from Belgium, Italy, and five studies from France occurring from January to December, 2020 and all used the PN plus panel version.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Excluded studies were comprised of 12 duplicates studies, 96 non-PN/PN plus Panel studies, 18 review articles or position statements, 17 non-clinical or non-human studies, two commentaries, three non-SARS-CoV-2 study, and one study due to insufficient data for evaluating incidence of co-detections related to PN Panel [Khurana et al, 2021] . After removing duplicate and non-applicable studies, seven studies with 558 patients were included for the systematic review and meta-analyses ( Table 1 , Supplementary Table 2) [ Camelena et al, 2021 , Kolenda et al, 2020 , Verroken et al, 2020 , Kreitmann et al, 2020 , Contou et al, 2020 , Foschi et al, 2021 , Maataoui et al, 2021 ]. Studies included a study from Belgium, Italy, and five studies from France occurring from January to December, 2020 and all used the PN plus panel version.…”
Section: Resultsmentioning
confidence: 99%
“…at ICU admit, upon intubation, within 48h of intubation, etc.). Four studies reported on timing of specimen collection including two studies noting an average collection 1 and 5 days after ICU admission, one study reporting an average of 3 hours after intubation, and one study with 33% of PN Panel testing within 48 hours of ICU admission [ Verroken et al, 2020 , Kreitmann et al, 2020 , Contou et al, 2020 , Maataoui et al, 2021 ]. Antibiotic use occurred in 28.1% to 79% of patients before respiratory specimens were obtained.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations